2009
DOI: 10.1016/j.ajhg.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Human Syndrome Implicates a Key Role for Intestinal Cell Kinase in Development of Central Nervous, Skeletal, and Endocrine Systems

Abstract: Six infants in an Old Order Amish pedigree were observed to be affected with endocrine-cerebro-osteodysplasia (ECO). ECO is a previously unidentified neonatal lethal recessive disorder with multiple anomalies involving the endocrine, cerebral, and skeletal systems. Autozygosity mapping and sequencing identified a previously unknown missense mutation, R272Q, in ICK, encoding intestinal cell kinase (ICK). Our results established that R272 is conserved across species and among ethnicities, and three-dimensional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 35 publications
2
94
0
Order By: Relevance
“…Human endocrine-cerebro-osteodysplasia (ECO) syndrome is an autosomal-recessive neonatal-lethal disorder associated with congenital developmental defects in multiple organ systems [1]. A homozygous loss-of-function mutation R272Q in the human ICK (intestinal cell kinase) gene, encoding a highly conserved and ubiquitously expressed serine/threonine protein kinase [2, 3], was identified as the causative mutation for ECO [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human endocrine-cerebro-osteodysplasia (ECO) syndrome is an autosomal-recessive neonatal-lethal disorder associated with congenital developmental defects in multiple organ systems [1]. A homozygous loss-of-function mutation R272Q in the human ICK (intestinal cell kinase) gene, encoding a highly conserved and ubiquitously expressed serine/threonine protein kinase [2, 3], was identified as the causative mutation for ECO [1].…”
Section: Introductionmentioning
confidence: 99%
“…A homozygous loss-of-function mutation R272Q in the human ICK (intestinal cell kinase) gene, encoding a highly conserved and ubiquitously expressed serine/threonine protein kinase [2, 3], was identified as the causative mutation for ECO [1]. ICK is very similar to MAP kinase in the catalytic domain and contains a MAPK-like TDY motif in its activation loop [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we examined outcomes of the ICK point mutation (R272Q) identified in human ECO syndrome (1). When mutant versions of ICK (R272A or R272Q) were overexpressed in cultured cells, primary cilia were significantly elongated (Fig.…”
Section: Ciliary Morphology and Shh Signaling Are Disrupted In Ick Tmmentioning
confidence: 99%
“…Six infants with ECO syndrome from a consanguineous Amish pedigree were observed to have multiple defects including hydrocephalus, holoprosencephaly, agenesis of the diencephalon, adrenal hypoplasia, and skeletal system defects such as cleft lip/palate, postaxial polydactyly, micromelia, hands with ulnar deviation, and bone underdevelopment (1). Genetic analysis of the infants with ECO syndrome revealed a missense mutation in a highly conserved C-terminal basic polar amino acid residue, Arg 272 , to neutral glutamine in the intestinal cell kinase (ICK) gene (1), which impairs the activation and subcellular localization of ICK in cultured cells. How these abnormalities in ICK result in pathological ECO syndrome phenotypes, however, remains unknown.…”
mentioning
confidence: 99%
“…In a different example, 70 phenotypic observations per patient were collected for a study of neonatal disorder with multiple phenotypic features. Hierarchical cluster analyses indicated that the neonatal disorder under study was likely a novel disorder when compared to six related congenital syndromes, and the data suggested a novel molecular mechanism [16,46] .…”
Section: Phenomicsmentioning
confidence: 99%